Teaching Quantitative Data Analysis with GNU PSPP: A Cognitive Apprenticeship Approach - Joanna Pitura (Acta Universitatis Wratislaviensis. Anglica Wratislaviensia)
The ability to analyse quantitative data using software is of great importance but represents a substantial challenge for many in the applied linguists’ community. One way to support them in this challenge is to provide inexperienced analysts with appropriate training. Accordingly, this methods tutorial paper aims to present the GNU PSPP open-source software and provide guidance on the development of analytic skills using this software among higher education students. The cognitive apprenticeship theory and research are addressed first as the theoretical foundation. What follows is a description of how cognitive apprenticeship approach was applied to teaching analytic practice in a Moodle-based course offered to graduate students enrolled in the TEFL MA programme at a university in Poland, where GNU PSPP was integrated in the coursework. The paper concludes with a brief evaluation of the course, showing that this approach works well for supporting students throughout the course and for enabling them to transition towards conducting quantitative data analysis using software in their own MA research projects. The paper may be of interest to those tasked with providing training and development programmes to students, faculty and researchers in applied linguistics and beyond, including those for whom access to commercial software may be of concern.